Satellite-based Tracking of Agricultural Adaptation Progress in Sub-Saharan Africa - Reymondin, Louis (2024)
Lack of systematic tools and approaches for measuring climate change adaptation limits the measurement of progress toward the adaptation goals of the Paris Agreement. To this end, we piloted a new approach, the Biomass Climate Adaptation Index (Biomass CAI), for measuring agricultural adaptation progress in Ethiopia across multiple scales using satellite remote sensing data. The Biomass CAI can monitor agri-biomass productivity associated with adaptation interventions remotely and facilitate more tailored precision adaptation. The Biomass CAI focuses on decision-support for end-users to ensure that the most effective climate change adaptation investments and interventions can be made in agricultural and food systems. This is the first implementation of such a system in Sub-Saharan Africa. It has not yet been validated and is presented here as preliminary results presenting the concept. This publication has been prepared as an output of CGIAR Research Initiative on Digital Innovation, which researches pathways to accelerate the transformation towards sustainable and inclusive agrifood systems by generating research-based evidence and innovative digital solutions. This publication has not been independently peer-reviewed. Any opinions expressed here belong to the author(s) and are not necessarily representative of or endorsed by CGIAR. In line with principles defined in CGIAR's Open and FAIR Data Assets Policy, this publication is available under a CC BY 4.0 license. © The copyright of this publication is held by IFPRI, in which the Initiative lead resides. We thank all funders who supported this research through their contributions to CGIAR Trust Fund.